Optimization of Social Media as a Counter to Islamophobia in Australia - Shinta Lailatul Maghfiroh; Siti Rohma (Kanal: Jurnal Ilmu Komunikasi, 2021)
Australia is a multicultural country, but Islamophobia is still developing, so it needs a way to stop that view. This study aims to prove that Islamophobia in the West can be minimized. This paper is a literature study with a political communication approach regarding the optimization of social media as a barrier to Islamophobia in Australia. Data collection comes from literature such as articles, journals, reports, policy briefs, news books, and other sources concerning social media and Islamophobia in Australia. Data analysis techniques were carried out with three stages namely data reduction, data presentation and verification. The object of study in this study is the optimization of social media to counter Islamophobia in Australia by Onepath Networks. The study results state that social media is quite optimal in order to minimize the development of Islamophobia issues. Onepath Network as one of the Islamic organizations in Australia, uses social media to preach. Da'wah is done with videos and documentaries that are shown on Youtube and even cinemas on Islamic dialogue. Since the Onepath Network was formed, Islamophobia in Australia began to diminish and is proven by Muslims who began to participate in various fields, including government, many mosques began to be built and many Islamic schools were established.